Piperacillin: Human Pharmacokinetics After Intravenous and Intramuscular Administration - Tjandramaga, T. B. (1978)
The pharmacokinetics of piperacillin were studied in a total of 26 Caucasian normal male volunteers. Single intramuscular doses of 0.5, 1.0, and 2.0 g were given to three groups, each containing eight volunteers. Mean peak serum concentrations of 4.9, 13.3, and 30.2 μg/ml were assayed at 30 to 50 min, and measurable levels were present up to 4, 6, and 8 h, respectively, after dosing. Single intravenous bolus doses of 1.0, 2.0, 4.0, and 6.0 g were given to four groups of five subjects, and mean serum concentrations of 70.7, 199.5, 330.7, and 451.8 μg/ml were measured at the end of the injections. The antibiotic had a mean terminal serum half-life of 60 to 80 min after the intramuscular doses and 36 to 63 min after intravenous administrations, depending on the dose. The apparent distribution volume was 20 to 24 liters/1.73 m(2), and distribution volume at steady state was 16 to 19 liters/1.73 m(2). Mean urinary recovery in 24 h was 74 to 89% for the intravenous doses and 57 to 59% for the intramuscular doses. The piperacillin-creatinine clearance ratios indicated that the proportion of renal excretion of piperacillin through tubular secretion was 56 to 73%, and this was confirmed by the renal clearance data from eight volunteers receiving probenecid treatment before the piperacillin dose. Probenecid (1 g given orally before administration of piperacillin) increased peak serum concentration by 30%, terminal serum half-life by 30%, and the area under the plasma concentration curve by 60%, and it decreased the apparent distribution volume by 20% and the renal clearance of the intramuscularly administered (1 g) antibiotic by 40%. Injections of piperacillin by both parenteral routes were well tolerated.